2013
DOI: 10.1037/a0031185
|View full text |Cite
|
Sign up to set email alerts
|

Sobering stories: Narratives of self-redemption predict behavioral change and improved health among recovering alcoholics.

Abstract: The present research examined whether the production of a narrative containing self-redemption (wherein the narrator describes a positive personality change following a negative experience) predicts positive behavioral change. In Study 1, we compared the narratives of alcoholics who had maintained their sobriety for over 4 years with those of alcoholics who had been sober 6 months or less. When describing their last drink, the former were significantly more likely to produce a narrative containing self-redempt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(131 citation statements)
references
References 80 publications
5
124
2
Order By: Relevance
“…In a study by Bauer and McAdams (2010), themes of communion in emerging adults’ stories of their personal goals were associated with increases in mental health three years later. In a study by Dunlop and Tracy (2013), Alcoholics Anonymous participants whose stories of their last drink included themes of redemption were more likely to report remaining sober four months later than those whose narratives did not contain this theme (Dunlop & Tracy, 2013). Finally, in a study by Lodi-Smith and colleagues (2009), low levels of themes of contamination (as part of a composite variable representing “affective processing”) in college students’ stories of their personality change during college were associated with increases in mental health over the four years (Lodi-Smith et al, 2009).…”
Section: Four Core Themesmentioning
confidence: 99%
“…In a study by Bauer and McAdams (2010), themes of communion in emerging adults’ stories of their personal goals were associated with increases in mental health three years later. In a study by Dunlop and Tracy (2013), Alcoholics Anonymous participants whose stories of their last drink included themes of redemption were more likely to report remaining sober four months later than those whose narratives did not contain this theme (Dunlop & Tracy, 2013). Finally, in a study by Lodi-Smith and colleagues (2009), low levels of themes of contamination (as part of a composite variable representing “affective processing”) in college students’ stories of their personality change during college were associated with increases in mental health over the four years (Lodi-Smith et al, 2009).…”
Section: Four Core Themesmentioning
confidence: 99%
“…For example, Dunlop and Tracy [2013] found that recovering alcoholics whose personal narrative of their last drink was redemptive were more likely to stay sober over time than those whose story did not follow this master narrative. Adler and colleagues [Adler et al, 2015] recently found that those individuals whose life stories were more redemptive had increasingly positive mental health over time.…”
Section: Structural Master Narratives (Sequences)mentioning
confidence: 99%
“…This story is one that moves from negative to positive, tragedy to triumph. McAdams [2013] has argued that there are certain types of redemptive narratives, such as atonement, upward mobility, liberation, and recovery [see also Benish-Weisman, 2009;Dunlop & Tracy, 2013]. Yet even with these different types of redemption, at base, redemption is a structure for a narrative.…”
Section: Structural Master Narratives (Sequences)mentioning
confidence: 99%
“…For example, individual differences in autobiographical narratives are associated with the successful maintenance of sobriety among alcoholics (Dunlop & Tracy, 2013) and the desistence from crime among ex-convicts (Maruna, 2001), and individual differences in the trajectory of narrative development precede changes in mental health among psychotherapy clients (Adler, 2012).…”
Section: Theoretical Framementioning
confidence: 99%